Artificial Intelligence Application and Financial Inclusion Nexus on Sustainable Development Goals (SDGs) in Nigeria - OMANKHANLEN, Alexander Ehimare; JEGEDE, Wuraola Pelumi; NWOBODO, Helen (Journal of Posthumanism, 2025)
This study evaluated Artificial Intelligence Applications and Financial Inclusion Nexus in Nigeria. Financial institutions have always had the problem of meeting the financial needs of the low-income group in society, though, they have done their best to meet their needs, their effort have not yielded good results. Getting individuals and businesses into the formal financial net has been a problem. The present SDGs as constituted rest more on inclusiveness, especially financial inclusion. The SDGs comprise an ambitious 17 goals. While the Sustainable Development Goals (SDGs) do not explicitly address financial inclusion, increased access to financial services is a crucial facilitator for achieving many goals. The financial institutions and products are not suited for the low-income group in society, in addition, rural dwellers do not have access to financial institutions and products. The study used survey instruments and interviews for data collection. That is. using the mixed research method with data from three hundred and eighty-four respondents selected from rural communities, financial institutions, and universities in South-West Nigeria. The data were analysed using descriptive statistics, confirmatory factor analysis, regression analysis, structural equation model (SEM), and narrative technique. The results indicate that AI applications have significantly impacted financial inclusion in South-West Nigeria. Based on this, the study recommended that financial institutions invest in building AI-enabled platforms in local languages that will respond to customers’ needs.